Survival on Adventure Island - "Adlam, Frances" (Hawthorn; Mimosa McGraw-Hill, 2007)
Max and Ruby are in the third round of THE BRAIN, the latest and greatest TV survivor show. This time, they have to survive on Adventure Island. What will they eat and drink? How can they reach the waterfall before super-duper athletes Zelda and Levi with their rippling ribs and bulging biceps?
Donated by "Book Planet", Dated 18-4-2025.
Keywords: Children's stories